2021
DOI: 10.3389/fpsyt.2021.689277
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Supplementation With Antioxidant Agents on Sleep in Autism Spectrum Disorder: A Review

Abstract: Autism spectrum disorder (ASD) is a heterogeneous neurodevelopmental condition, whose etiology remains poorly understood in most cases. Several genetic, epigenetic and environmental factors have been implicated in ASD pathogenesis and numerous studies have provided evidences for increased levels of oxidative stress and reduced antioxidant capacity in patients with ASD. Recent clinical trials explored supplementation with antioxidant agents as a potential therapeutic strategy for ASD, investigating the impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 43 publications
2
16
0
Order By: Relevance
“…Multiple studies of melatonin (e.g., both immediate-release and extended-release) in ASD have shown that melatonin decreases the time to sleep onset, increases sleep duration, and decreases nighttime awakenings. The nighttime administration of melatonin was also shown to improve daytime behaviors in children with ASD [ 14 , 15 , 16 ]. However, some research has shown that melatonin use in children may affect hormonal development, mainly delaying the onset of puberty [ 17 ].…”
Section: Effectiveness Of Exogenous Melatoninmentioning
confidence: 99%
“…Multiple studies of melatonin (e.g., both immediate-release and extended-release) in ASD have shown that melatonin decreases the time to sleep onset, increases sleep duration, and decreases nighttime awakenings. The nighttime administration of melatonin was also shown to improve daytime behaviors in children with ASD [ 14 , 15 , 16 ]. However, some research has shown that melatonin use in children may affect hormonal development, mainly delaying the onset of puberty [ 17 ].…”
Section: Effectiveness Of Exogenous Melatoninmentioning
confidence: 99%
“…These changes in the mechanisms of absorption, or the permeability of the intestinal epithelial mucosa, can lead to an inflow of toxic or foreign organic or inorganic substances causing changes in immunological or metabolic defenses. That can ultimately affect the nerve pathways at the level of the large gastrointestinal nervous complex, or extend directly or indirectly to the central nervous system [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…People with ASD are exposed to the negative effects of chemical and environmental risks, such as aluminium from food packaging and cadmium from air pollution [ 7 ]. Since several studies report that ASD people struggle to eliminate toxins from the body, there may be an increased probability of a positive effect from taking antioxidant supplements [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…614 It has been postulated that misalignment of melatonin rhythm is involved in the etiology of these sleep problems, a crucial component of circadian rhythm regulation, including sleep-wake cycles. 1,1520…”
mentioning
confidence: 99%
“…3 Of the drugs used in therapy, melatonin deserves special consideration, not only because it is one of the most commonly used pharmacologic treatments but also because it is frequently sold as a nutritional supplement although it has been relatively underexamined. 16,17,22,23…”
mentioning
confidence: 99%